Community engagement, shared knowledge, and resilience: Implications for the COVID-19 pandemic and beyond. Issue 1 (1st March 2022) - Koff, Harlan; Maganda, Carmen
Abstract : As has become our tradition, we begin this new issue by wishing our readers a happy new year in 2022. This editors' note introduces volume 12 of Regions & Cohesion, our second as an open access journal. Already we view 2022 as a promising new year. The COVID-19 pandemic is still with us, but we are showing signs of adaptation at different levels. The arrival of the Omicron variant has resulted in fewer fatalities than previous variants. New vaccines and alternative treatments are being developed, and despite numerous logistical, political, and ideological challenges, the percentage of the vaccinated global population is increasing (Shet et al., 2022 ). These developments, combined with promising research on neonatal immunity and children's immune tolerance indicate that we are heading in the direction of increased resilience.